Development of a Web-Based Industrial Training Student Activity Management System - Wan Hussain Wan Ishak; Siti Nur Aisyah binti Abdullah (CV Media Inti Teknologi, 2025)
Background of study: Industrial training is essential for bridging academic knowledge and workplace practice, equipping students with technical and soft skills required for future employment. However, traditional documentation methods such as manual logbooks are often inefficient, error-prone, and limit effective supervision and timely feedback. Aims and scope of paper: This paper presents the development of the Web-Based Industrial Training Student Activity Management System (WIT), designed to streamline industrial training management at the School of Computing, Universiti Utara Malaysia. The system aims to enhance communication, ensure accurate reporting, and support sustainable digital supervision. Methods: The WIT system was developed using the Waterfall Model, with stakeholder input incorporated at each stage of requirements, design, development, testing, and maintenance. Usability testing was conducted with 30 participants (students and staff) using the WAMMI framework, which evaluates five key usability dimensions. Result: The evaluation results demonstrated high levels of user satisfaction across all metrics: Attractiveness (91.67%), Controllability (97.5%), Helpfulness (94.17%), Efficiency (92.5%), and Learnability (96.67%). These findings confirm that WIT provides an effective, user-friendly platform for activity logging, reporting, and supervision. Conclusion: WIT successfully addresses challenges in traditional training management by promoting transparency, accountability, and efficient supervision. The system contributes to ICT-driven educational innovation and has strong potential for future scalability, including mobile integration and advanced analytics.